Vênus em quarto crescente / Tão profundo quanto olhos obsidianos / Azuis fecundos - Santos, Roberta Dos (Das Questões, 2018)
Vênus em quarto crescente / Tão profundo quanto olhos obsidianos / Azuis fecundos